DIMENSÕES DO APOIO SOCIAL E PRÁTICA DE ALEITAMENTO MATERNO: ESTUDO PRÓ-SAÚDE - Lucilene Antônio Afonso Bertoldo; Cristiano Siqueira Boccolini; Eduardo Faerstein (Universidade do Estado do Rio de Janeiro, 2019)
Objective: To estimate the association between social support and its dimensions and the prevalence of breastfeeding (BF) in the first two years of life. Methods: Cross-sectional study with women (n = 1,634) participating in the Phase 1 of the Pró-Saúde Study (1999), with information collected through a self-completed questionnaire. The duration of breastfeeding was self-reported in months and, subsequently, prevalence rates were assessed at 6, 9, 12 and 24 months of age. Social support was assessed in three dimensions: positive social interaction / affective, information / emotional support, and material support. Odds ratios with 95% confidence intervals were estimated by logistic regression, adjusted for maternal confounders, with the outcome being the prevalence of breastfeeding in each age. Results: The prevalence rates of breastfeeding at 6, 9, 12 and 24 months of age were 58.0%, 31.9%, 23.5% and 9.7%, respectively. The positive social interaction/affective dimension was the most important one for breastfeeding at six months (OR = 1.52 95%CI = 1.03-2.25) and also for breastfeeding at 24 months (OR = 2.38 95%CI = 1.03-5.49). Conclusion: Social support is an important aspect to be considered when giving support to the breastfeeding woman, especially in the first months of a child's life. DOI: 10.12957/demetra.2019.43037